The Influence of Agricultural Extension Services and Livelihood Capitals on Farmers' Climate Resilience in West Java, Indonesia: A Structural Equation Modeling Approach - Azhari, Rafnel; Amanah, Siti; Fatchiya, Anna; Kinseng, Rilus A (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
This study analyzes how agricultural extension services and various forms of livelihood capital influence rice farmers' climate resilience and farm sustainability in West Java, Indonesia. 371 Karawang and Subang Regencies respondents were surveyed using a structured questionnaire covering farmers engaged in intensive and semi-intensive rice production systems. The study employed Structural Equation Modeling using Partial Least Squares (SEM-PLS) to assess the direct and indirect effects of human, social, natural, financial, and physical capitals and extension services on resilience capacity and farming sustainability. The results show that human capital, natural capital, social capital, financial capital, and extension services all significantly positively affect resilience capacity. In turn, resilience capacity is a key mediating variable contributing to farm sustainability. Among the variables analyzed, agricultural extension services strongly influenced sustainability outcomes. Furthermore, the Importance-Performance Map Analysis (IPMA) reveals that financial and natural capital are high-priority areas for intervention due to their strategic influence and current performance gaps. These results underscore the need to enhance farmer access to inclusive and adaptive financial services, improve natural resource governance, and strengthen the quality and contextual relevance of agricultural extension. The study recommends a shift toward a pluralistic and resilience-oriented extension model that integrates local knowledge, livelihood assets, and climate adaptation strategies to build sustainable and climate-resilient farming systems.